The Poetics of Transience in Marjorie Evasco’s Skin of Water: Selected Poems - Lua, De La Salle University, Philippines, Shirley O. (Asiatic: IIUM Journal of English Language and Literature, 2011)
This article seeks to examine the poetics of transience manifested in the poetry of Marjorie Evasco. She is the 2010 SEA Write Award winner from the Philippines who writes both in English and Visayan Cebuano. The article focuses on several selected poems from her recent collection, Skin of Water: Selected Poems (2009). It underscores how Evasco's poetic situations reflect on life's transitory character – the brevity of relationship, the fragility of a child's body, the passing of pain, an encounter with trees and the inevitability death. It also investigates how Evasco's poetic vision imagines ways of confronting the transient and even triumphing over it. The poet has resorted to clever and creative stratagems, such as conjuring images of things ephemeral, the naming of things to hold dominion over them, the manipulation of rhythmic breaks, the deployment of metamorphic imaging and the evocation of deep emotions of love, pain and joy.